Cholinergic modulation supports dynamic switching of resting state networks through selective DMN suppression - Sanda, Pavel; Hlinka, Jaroslav; van den Berg, Monica; Skoch, Antonin; Bazhenov, Maxim; Keliris, Georgios A; Krishnan, Giri P (PLoS computational biology, 2024)
Brain activity during the resting state is widely used to examine brain organization, cognition and alterations in disease states. While it is known that neuromodulation and the state of alertness impact resting-state activity, neural mechanisms behind such modulation of resting-state activity are unknown. In this work, we used a computational model to demonstrate that change in excitability and recurrent connections, due to cholinergic modulation, impacts resting-state activity. The results of such modulation in the model match closely with experimental work on direct cholinergic modulation of Default Mode Network (DMN) in rodents. We further extended our study to the human connectome derived from diffusion-weighted MRI. In human resting-state simulations, an increase in cholinergic input resulted in a brain-wide reduction of functional connectivity. Furthermore, selective cholinergic modulation of DMN closely captured experimentally observed transitions between the baseline resting state and states with suppressed DMN fluctuations associated with attention to external tasks. Our study thus provides insight into potential neural mechanisms for the effects of cholinergic neuromodulation on resting-state activity and its dynamics.
Keywords: Connectome; Male; Models, Neurological; magnetická rezonanční tomografie; Nerve Net; Brain; výpočetní biologie; modely neurologické; Computer Simulation; Adult; dospělí; mužské pohlaví; Acetylcholine; Rest; odpočinek; lidé; Humans; nervová síť; default mode network; konektom; mozek; acetylcholin; počítačová simulace; Default Mode Network; Magnetic Resonance Imaging; Computational Biology